Philippine Air Transport Infrastructure: State, Issues, Government Strategies - Kris A. Francisco; Valerie L. Lim (Philippine Institute for Development Studies (PIDS), 2022)
The air transport sector is important in facilitating economic growth and development. In a country made up of more than 7,000 islands, air transportation serves as the fastest mode of connectivity within the country and the rest of the world. The direct impact of the air transport sector to Philippine GDP may appear small at 0.61 percent in 2019; but its enabling role for high-value industries such as trade, manufacturing and tourism justifies the need to prioritize this sector. Having sufficient, well-functioning and efficient air transport infrastructure is necessary to ensure maximum benefits to the economy. The country's air transport infrastructure, however, suffers from capacity and technical capability constraints. While the government recognizes the need to improve the country's air transport infrastructure through the provision of new airports, and improving existing facilities and technical capabilities, time is crucial and huge investments are needed to catch up with the burgeoning demand for air travel.
Keywords: 330; air transport sector; air transport policy; airports